Modern Aspects of Analgosedation in Critically ill Patients - Kobelyatskyi, Yu (Pain medicine, 2025)
Introduction. In contemporary intensive care units, clinical practice is shifting from prolonged deep sedation with benzodiazepines and opioids toward lighter, controlled, and «cooperative» sedation. This change is driven by the association of deep sedation with an increased risk of delirium, longer duration of mechanical ventilation, higher mortality, and adverse long-term outcomes. At the same time, the role of analgosedation with minimal use of benzodiazepines and an emphasis on maintaining patient interaction is increasing. The aim of this work is to summarize modern aspects of analgosedation in critically ill patients, focusing on the pharmacological properties of midazolam and dexmedetomidine and analyzing their use in anesthesiology and intensive care. The objectives of the work are to outline the evolution of sedation approaches in intensive care units, to describe the pharmacodynamic and pharmacokinetic characteristics of midazolam, to analyze its potential for sedation of varying depth, and to compare it with the effects of dexmedetomidine. The article also considers the specific features of using these agents in clinical situations requiring prolonged, controlled, or sequential sedation. Conclusions. Analgosedation is a key component of managing critically ill patients, and modern approaches aim to reduce the depth of sedation and avoid the routine use of benzodiazepines. Midazolam remains an important agent for short-term sedation, induction of anesthesia, anterograde amnesia, rescue sedation, and control of anxiety and seizures, although analgosedation generally requires its combination with opioids. Dexmedetomidine provides dose-dependent sedation while preserving patient interaction, has minimal respiratory depressive effects, modulates sleep and sympathetic activity, and can be used in sepsis, septic shock, delirium, and withdrawal states, which aligns with modern concepts of cooperative sedation. Sequential use of midazolam and dexmedetomidine may be effective when prolonged sedation is required in selected patients